Pronomina Persona dalam Lirik Lagu the Sketchbook: Sebuah Kajian Nilai dan Relasi Manusia Melalui Bahasa: Personal Pronouns in the Sketchbook Song Lyrics: A Study of Human Values and Interpersonal Relationships Through Language - Naufal Arifudzaki; Syihabuddin (Undiksha Press, 2026)
Many songs carry personal pronouns that musicians use to deliver their messages, yet listeners rarely pay attention to them. This study analyzed the use of personal pronouns in song lyrics, the meanings behind their selection, and the axiological values they carry. A qualitative descriptive approach was used to examine Japanese personal pronouns across five songs from The Sketchbook's album Sketchbook : Kakusei, Colors, Kiwoku, Birthday, and Mirai e. The theoretical framework drew on Iori's account of Japanese personal pronouns, Chaer and Muliastuti's semantic theory, and Scheler's axiological classification. Data were collected through careful listening and systematic notation. The findings show that The Sketchbook uses three personal pronouns across the five songs: boku with 14 data, kimi with 9 data, and bokura with 6 data, totaling 29 data. Each pronoun serves different functions, shifting between the songwriter's own perspective and the person being addressed. In terms of axiology, all three pronouns predominantly reflect spiritual values, as the lyrics deal with self-awareness, human connection, and questions of meaning.